Activin B signaling may promote the conversion of normal fibroblasts to scar fibroblasts. Issue 24 (12th June 2020) - Deng, Shi-Kang; Tang, Jian-Zhong; Jin, Yan; Hu, Ping-Hai; Wang, Jun-Feng; Zhang, Xiao-Wen
Abstract : Abstract: This study is to explore the molecular mechanism of benign bile duct hypertrophic scar formation. Differential proteins between the normal fibroblast (NFB) and scar fibroblast (SCFB) were screened by protein chip assay, and analyzed by pathway-enrichment analysis and function-enrichment analysis. The differential proteins were further tested by ELISA. SiRNA-Act B was transfected to SCFB to down-regulate the expression of Act B. NFB was incubated with rh-Act B. The cell apoptosis and cell cycle were determined by flow cytometry. The expression of Act B, Smad2/3, transforming growth factor-β1 (TGF-β1), endothelin-1 (ET-1), thrombospondin-1 (Tsp-1), and Oncostatin M (OSM) were detected by Western blot. A total of 37 differential proteins were identified in SCFBs by microarray ( P  < .05), including 27 up-regulated proteins and 10 down-regulated proteins ( P  < .05). Their function were associated with Activin signaling, synthesis and degradation of extracellular matrix, formation and activation of cytokine, inflammatory reaction, immunoreaction, tissue damage reaction, cell cycle, migration, apoptosis, and secretion, etc. ELISA results showed that the expression of Act B, TGF-β1, ET-1 were higher in SCFBs, while the expression of Tsp-1 and OSM were lower in SCFBs ( P  < .05). After interfered by siRNA-Act B, the expression of Act B mRNA decreased ( P  < .05). The percentage of early apoptosis increased ( P  < .05). The expression of Act B, Smad2/3, TGF-β1 were decreased and Tsp-1, OSM were increased ( P  < .05). After treatment with rh-Act B, the percentage of G0/G1 phase of NFBs was decreased and that of S phase was increased without significance ( P  > .05). The expression of Act B, Smad2/3, TGF-β1 were increased ( P  < .05) and Tsp-1, OSM were decreased ( P  < .01). There are differentially expressed proteins between SCFBs and NFBs. Activin B signal plays an important role in the process of NFB transforming to SCFB, and TGF-β1, Smad2/3, Tsp-1, and OSM are important participants.